Bipolar Disorder in Adolescents: Clinical Manifestations, Causes, and Comprehensive Management Strategies - Baiq Annisa Ulfi Anggraeni; Aisya Nur Abida; Najla Firyal Husna; Komang Puspa Dewi; Alifa Aswandani; Muhammad Rezky Audia Aunurrahman; Azizatul Adni; Atsila Shofa, Dhiya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Bipolar disorder in adolescents is a common mental health condition characterized by extreme mood swings between manic and depressive episodes. This condition significantly impacts psychosocial aspects and quality of life. The purpose of this article is to describe the clinical manifestations of bipolar disorder in adolescents, understand its etiology and pathophysiology, and review its management. The method used is a literature review of various sources relevant to the topic. The review indicates that bipolar disorder is influenced by genetic, neurochemical, and environmental factors. Early detection and appropriate interventions are needed to prevent worsening of this condition. Management can be carried out through a combination of pharmacotherapy, such as lithium and quetiapine, along with psychotherapy and regular monitoring to optimize treatment outcomes and improve the quality of life for adolescents with bipolar disorder.